Temperature mediated the balance between stochastic and deterministic processes and reoccurrence of microbial community during treating aniline wastewater. (1st August 2022) - Chen, Hui; Chen, Zhu; Chu, Xueyan; Deng, Yan; Qing, Shengqiang; Sun, Chongran; Wang, Qi; Zhou, Hongbo; Cheng, Haina; Zhan, Wenhao; Wang, Yuguang
Highlights: High aniline removal was achieved under simulated seasonal temperature changes. Microbial diversity and structure recovered with temperature returned to 30 °C. Temperature regulated the balance between stochastic and deterministic processes. Keystone taxa of OTU0356 recurred when the temperature was dropped to 30 °C. Abstract: Seasonal temperature changes significantly affect microbial community diversity, composition, and performance in wastewater treatment plants. However, the community assembly mechanisms under seasonal temperature variations remain unclear. Here, we carried out temperature cycling experiments (30 °C, 35 °C, 37 °C, 40 °C, 42 °C, 45 °C, 40 °C, and 30 °C) to investigate how temperature impacts microbial performance and co-occurrence network and how assembly processes determine the structure and function of microbial communities during treating aniline wastewater. During the 195-day operation, the system achieved an efficient and stable aniline removal of 99%. Interestingly, α-diversity and network complexity were negatively correlated with temperature but could be recovered when the temperature was returned to 30 °C. The results showed that functional redundancy was probably responsible for the excellent microbial performance during the whole process. Null model analyses presented that deterministic process dominated the community when the temperature was 30 °C, and stochasticity dominated the assembly process when the temperature was over 30 °C. Overall, the balance between stochastic and deterministic processes in the treatment of aniline wastewater mediated the reoccurrence of microbial community and co-occurrence network at different temperatures. This study provides new insights into microbial community reoccurrence under seasonal temperature changes and a theoretical basis for regulating microbial communities in wastewater treatment plants. Graphical abstract: Image, graphical abstract